An Attempt to Polarize Human Neutrophils Toward N1 and N2 Phenotypes in vitro - Ohms, Mareike; Möller, Sonja; Laskay, Tamás (Frontiers in Immunology, 2020)
Neutrophils act as the first line of defense against invading pathogens. Although traditionally considered in context of their antimicrobial effector functions, the importance of tumor-associated neutrophils (TANs) in the development of cancer has become increasingly clear during the last decade. With regard to their high plasticity neutrophils were shown to acquire an anti-tumorigenic N1 or a pro-tumorigenic N2 phenotype. Despite the urgent need to get a comprehensive understanding of the interaction of TANs with their tumor microenvironment most studies still rely on murine tumor models. Here we present for the first time a polarization attempt to generate N1 and N2 neutrophils from primary human neutrophils in vitro. Our results underscore that N1-polarized neutrophils have a pro-inflammatory phenotype characterized among others by a higher level of ICAM-1 and high secretion of IP-10/CXCL10 and TNF. Further we demonstrate that neutrophils incubated under a tumor-mimicking in vitro-environment show high cell surface expression of CXCR2 and secrete high levels of IL-8. These findings suggest that it is feasible to polarize blood-derived primary human neutrophils towards N1- and N2-like phenotypes in vitro. Further we hypothesized that the presence of anti-inflammatory neutrophil phenotype is not a phenomenon limited to cancer but also occurs when neutrophils are infected with intracellular pathogens. Indeed our findings indicate that N2-polarized neutrophils exert a markedly decreased capacity to kill the protozoan parasite L. donovani, and therefore permit parasite persistence.